PERBEDAAN PERSEPSI TENTANG ETIKA BISNIS PADA MAHASISWA YANG BELUM DAN SUDAH MEMPELAJARI MATA KULIAH ETIKA BISNIS PADA PRODI AKUNTASI DI PERGURUAN TINGGI KOTA BATAM - Hajan Hidayat; Dinda Anastasyah (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2017)
Business ethics is the knowledge about the procedures for setting up and managing ideal business into consideration the norms and morality universally applicable and economically or socially. The application of these norms and morality support the purpose and goals in business activities. This study aims to determine whether there are differences between the perceptions of business ethics and students who have already studied the subjects of business ethics in the accounting department of a university in the city of Batam. Samples are 185 regular grade student accounting Prodi morning at an accredited university in the city of Batam. Testing the hypothesis in this study using a statistical test Independent sample T-test contained in SPSS 22.0 and the results show that there are differences between the perceptions of business ethics and students who have already studied the subjects of business ethics. This study shows that business ethics education affects the perception of students so that students who have followed the course of business ethics have a different perception of students who have not followed the course of business ethics. Limitations of this study is the sample used only students of accounting in Batam alone. Business ethics education is very important to be a provision for students and should be maximized curriculum. Suggestions for further research should be expanded samples studied, such as using student of accounting in Riau Islands and also add other variables in the study.